High-Risk Repair of Traumatic Mitral Valve Rupture in the Setting of Polytrauma - Paisley, Michael John; Deboard, Zachary; Thomas, Donald (The Thoracic and Cardiovascular Surgeon Reports, 2018)
Background The rare complication of mitral valve rupture from blunt trauma is certainly not at the top of the differential of shock.Case Description We report the case of a 56-year-old woman who sustained numerous injuries after a 30-m fall with cardiogenic shock secondary to mitral valve rupture causing severe mitral valve regurgitation. Management included successful primary leaflet repair, annuloplasty, and single vessel coronary artery bypass.Conclusion Valvular repair in the setting of polytrauma is a complex decision that requires careful balance of risks and benefits relative to patient stability.
Keywords: MV surgery; trauma; shock: systemic; cardiac or circulatory; myocardial injury: blunt; penetrating; and iatrogenic